Do Innovation in Environmental-Related Technologies and Renewable Energies Mitigate the Transport-Based CO2 Emissions in Turkey? - Alnour, Mohammed (Frontiers in Environmental Science, 2022)
Given the unprecedented level of air pollution in urban areas, currently, green transport system has been a subject to an important debate in academic and policymaking circles. Despite the considerable outputs provided by the attendant literature, however, the empirical studies have relied on conventional econometric models in which structural shocks are not controlled. Therefore, this study aims to offering a new perceptive of the dynamic connection between renewable energy, environment-related technological innovation, and transport-based CO2 emissions in Turkey during 1990Q1 to 2014Q1 by applying Structural Vector Autoregressive approach (SVAR). This novelty approach helps to solve a problem that the earlier method could not do so. Furthermore, to explore the co-movements and the lead-lag interrelations among the study variables, the wavelet coherence technique is used. The findings disclose that environment-related technological innovation have no reliable power in explaining the variation in CO2 emissions from transport sector. Solar energy is found to impact the CO2 emissions positively in the long run, while biofuels hold the same effect in short run. Moreover, the per capita GDP and urbanization significantly impact the carbon emissions from transport system in long run with a negative sign. The lead-lag analysis reveals that transport-based CO2 emissions is lagging in renewables and green technological innovation. Fourth and sixteenth periods are the most dominant frequencies. Accordingly, numerous recommendations for policy formulation and scope for future research have been provided.